Pengaruh Suhu Pengukusan Pada Pengepresan Biji Bunga Matahari Terhadap Rendemen Dan Mutu Minyak Yang dihasilkan (Bagian KeDua)) - Anang Lukmana (Jurnal Kimia dan Kemasan, 1978)
The effect of steaming temperatures of husked sunflower seed on the yield and quality of the oil have been studied using a Iocal varaety "Rembang". The oil was extracted by pressing at 18,00 psi for 10 minutes. The results show that higher steaming temperatures increased the peroxide number, saponfication number and free fatty acid, and decreased the moisture content. The steaming temperature of 95° C produced the optimurn yield and quality.